Pengaruh Deterjen Cair terhadap Mortalitas dan Perilaku Ikan Nila (Oreochromis niloticus): The Effect of Liquid Detergent on Mortality and Behavior of Nila Fish (Oreochromis niloticus) - Amaliah, Rizki; Hanifa, Lola Nur; Emil, Muhammad Farhan Putra; Dheana Puspa Dewi; Widarto, Tri Heru; Dewi, Dheana Puspa (Departemen Biologi, Institut Pertanian Bogor, 2024)
The disposal of detergent waste into water bodies leads to environmental problems. The use of detergents is increasing, and the variety of detergents available is also becoming more diverse. This study examines the mortality and behavior of Nile tilapia (Oreochromis niloticus) in response to liquid detergent contaminants. The research was conducted from March to April 2023 at the Fish Behaviour Laboratory, Faculty of Fisheries and Marine Sciences, IPB University. We used 154 individuals of Nile tilapia measuring 5-7 cm. A total of 90 individuals were used for the preliminary test and most of them died at the highest concentration of 100 ml/L within five minutes. Sixty individuals were used for determining LD50–96 and we found that the LD50–96 was 1.29 ml/L. The behavior of four individuals of tilapia was observed using focal animal sampling in four sublethal concentrations. The results show that the detergent contaminant inhibits oxygen diffusion and damages the physiological functions of the tilapia. The detergent concentration level also affects the operculum opening and closing behavior, movement, feeding response, and mortality.